1997
DOI: 10.1161/01.cir.96.12.4343
|View full text |Cite
|
Sign up to set email alerts
|

Small Heat Shock Proteins and Protection Against Ischemic Injury in Cardiac Myocytes

Abstract: The increased expression of hsp27 and alphaB-crystallin through an adenovirus vector system protects against ischemic injury in adult cardiomyocytes. Likewise, the overexpression of alphaB-crystallin protects against ischemic damage in neonatal cardiomyocytes. Decreasing the high levels of endogenous hsp25 present in neonatal cardiomyocytes renders them more susceptible to damage caused by simulated ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
212
0
12

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(229 citation statements)
references
References 32 publications
5
212
0
12
Order By: Relevance
“…68 When a cell is subjected to stress, alphaB-crystallin protects muscle fibers from the effects of ischemia. 69 AlphaBcrystallin participates in a number of other cellular processes, helping to modulate correct protein-folding, compartment-targeting, degradation and signaling.…”
Section: Cryab and Alphab-crystallinmentioning
confidence: 99%
“…68 When a cell is subjected to stress, alphaB-crystallin protects muscle fibers from the effects of ischemia. 69 AlphaBcrystallin participates in a number of other cellular processes, helping to modulate correct protein-folding, compartment-targeting, degradation and signaling.…”
Section: Cryab and Alphab-crystallinmentioning
confidence: 99%
“…Actin, in particular, has been found to be protected by the small HSPs [Snoeckx et al, 2001], which is important not only for the cytoskeleton of all cells, but also for the sarcomeres in cardiac tissue. In addition to preconditioning studies, which tend to induce a variety of protective stress proteins, transgenic studies in vitro [Martin et al, 1997;Brar et al, 1999;Vander Heide, 2001] have demonstrated that increasing levels of Hsp25/27 prior to simulated ischemia-reperfusion injuries can have a protective effect. Miyakawa et al [2001] found that the temperature required for a given expression of a reporter gene (lacZ) under HSP16 promoter control in transgenic nematode worms was reduced after exposure to a 60 Hz magnetic field at up to 0.5 T. Leszczynski et al [2002] saw an increase in protein phosphorylation and Hsp27 expression after exposure to a 900 MHz GSM signal.…”
Section: Mechanisms: Heat Shock Proteinsmentioning
confidence: 99%
“…Concerning the role of phosphorylation on HSP function other studies have shown that HSP27 oligomerization and chaperone function are down regulated by phosphorylation [28] and HSP70 phosphorylation is significantly reduced by heat stress [29]. HSP90 phosphorylation plays an important role on the stimulation of eIF-2a kinase activity [15] and on the regulation of the interaction with pp60v-src [16].…”
Section: Polyacrylamide Gel Electrophoresismentioning
confidence: 99%